2023
DOI: 10.1097/meg.0000000000002572
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic impact of gamma-glutamyl transpeptidase to platelets ratio on hepatocellular carcinoma patients who have undergone surgery: a meta-analysis and systematic review

Abstract: Gamma-glutamyl transpeptidase to platelet ratio (GPR) is an inflammatory index and has been used as a prognostic index for a variety of tumors. However, the association between GPR and hepatocellular carcinoma (HCC) still remained controversial. Therefore, we performed a meta-analysis to determine the prognostic impact of GPR on HCC patients. PubMed, Embase, Cochrane Library, Web of Science, the Chinese National Knowledge Infrastructure, Wanfang Database, Chinese VIP Database, the US Clinical Trials Registry, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…Elevated GGT levels have been implicated in tumor formation and progression through various mechanisms [ 15 ]. Consequently, previous studies have recommended utilizing the GGT to platelet ratio as a prognostic marker for HCC patients [ 16 , 17 ]. Additionally, individuals with malignant tumors often experience compromised nutritional status due to heightened metabolism and chronic inflammation [ 18 ], leading to decreased PA levels.…”
Section: Discussionmentioning
confidence: 99%
“…Elevated GGT levels have been implicated in tumor formation and progression through various mechanisms [ 15 ]. Consequently, previous studies have recommended utilizing the GGT to platelet ratio as a prognostic marker for HCC patients [ 16 , 17 ]. Additionally, individuals with malignant tumors often experience compromised nutritional status due to heightened metabolism and chronic inflammation [ 18 ], leading to decreased PA levels.…”
Section: Discussionmentioning
confidence: 99%
“…The conclusions drawn between different studies are also inconsistent, and the best cutoff values are also different. [18][19][20] In addition, some previous studies have suggested that aminotransferase-to-platelet ratio (APRI) [21][22][23] and gamma-glutamyl transferase-to-platelet ratio (GPR) [24][25][26] are independent risk factors for shorter survival and higher recurrence after HCC surgery. However, it is still uncertain whether preoperative APRI or GPR can predict MVI in solitary HCC, and there is no report on the relationship between APRI/GPR and MVI.…”
Section: Introductionmentioning
confidence: 99%
“…39 Several previous studies have shown that APRI and GPR were independent risk factors for shorter OS and high recurrence after HCC surgery. [21][22][23][24][25][26] Additionally, a recent meta-analysis (4706 HCCs) showed a significant correlation between preoperative GPR and postoperative prognosis in HCC patients, with higher GPR closely associated with poorer OS (HR: 1.79; P<0.001). 26 However, MVI is the most direct predictive signal for early intrahepatic micrometastasis in HCC and the most important source of tumor recurrence or poor prognosis.…”
mentioning
confidence: 99%
See 1 more Smart Citation